Potential Mechanisms of Methylglyoxal‐Induced Human Embryonic Kidney Cells Damage: Regulation of Oxidative Stress, DNA Damage, and Apoptosis. Issue 2 (18th January 2022) - Liu, Dan; Cheng, Ye; Tang, Zhipeng; Chen, Junliang; Xia, Ying; Xu, Chengbin; Cao, Xiangyu
Abstract: Methylglyoxal (MGO) is a reactive carbonyl species that can cause cellular damage and is closely related to kidney disease, especially diabetic nephropathy. The toxic effect of MGO (0.5, 1, and 2 mM) on human embryonic kidney (HEK293) cells and its underlying mechanisms were explored in this study. Cell viability, apoptosis and the signaling pathways were measured with MTT, fluorescent staining and western blot experiments, the results showed that MGO could induce oxidative stress and cell inflammation, the level of reactive oxygen species (ROS) increased, and p38MAPK, JNK and NF‐κB signaling pathways were activated. Meanwhile, MGO also induced DNA damage. The expression of DNA oxidative damage marker 8‐hydroxy‐2'‐deoxyguanosine (8‐OHdG) increased, the expression of double‐strand break marker γH2AX increased significantly, and ATM/Chk2/p53 DNA damage response signaling pathway was activated. Furthermore, the expression of the receptor for advanced glycation end products (RAGE) also increased. Finally, mitochondrial membrane potential (MMP) decreased, fluorescence intensity of Hoechst33258 increased, and the protein expression ratio of Bax/Bcl‐2 increased significantly after the treatment of MGO. These results demonstrated that MGO might induce HEK293 cells damage by regulating oxidative stress, inflammation, DNA damage, and cell apoptosis, which revealed the specific mechanisms of MGO‐induced damage to HEK293 cells. Abstract :